Tip sheet gender-inclusive approaches in the energy sector. (Metro Manila, Philippines Asian Development Bank, 2018)
The Gender Tip Sheets are reference guides for staff and consultants of ADB and its developing members for conceptualizing, designing, and implementing gender-inclusive projects.
Keywords: Energy; Gender equality; Electronic books